Effects of a back-assist exosuit in lab-based approximations of construction tasks performed by novices and experienced construction workers. - Song, Yu; Goršič, Maja; Feng, Zhichen; Cordova, Haylen; Li, Ling; Dai, Boyi; Novak, Vesna (Ergonomics, 2025)
Passive back-assist exosuits may be beneficial for construction workers, but few evaluations have been conducted with actual workers and construction-relevant tasks. This paper presents a laboratory study of the HeroWear Apex exosuit with 35 participants: 15 with significant construction experience and 20 without it. Participants completed several approximations of brief construction tasks (lifting, carrying, raising boards) and three 3-min tasks (hunched standing, kneeling, hunched walking with a nail gun) with and without the exosuit. During brief tasks, erector spinae electromyograms were reduced in all tasks (Cohen's d up to −0.58), kinematics suggested load shifting from the back to the legs, and the exosuit was perceived as helpful. During 3-min tasks, the exosuit was perceived as helpful in all tasks, but only reduced erector spinae electromyograms during kneeling. Thus, the exosuit may benefit workers during several construction-related tasks, though objective benefits could not be shown in 3-min standing or walking. Practitioner summary: This study explored how a passive back-assist exosuit affects back muscle activity and kinematics in lab-based approximations of construction tasks performed by both novices and experienced construction workers. Quantitative and qualitative results indicated potential benefits in several brief load lifting and carrying tasks, but not during 3-min standing or walking.